Reliability and Validity of the Persian Version of Compulsive Eating Scale (CES) in Overweight or Obese Women and its Relationship with Some Body Composition and Dietary Intake Variables - Seyed-Ali Mostafavi; Seyed Ali Keshavarz; MohammadReza Mohammadi; Saeed Hosseini; Mohammad Reza Eshraghian; Payam Hosseinzadeh; Maryam Chamari; Zeinab Sari; Shahin Akhondzadeh (Iranian Journal of Psychiatry, 2016)
Objective: Compulsive or binge eating is a kind of disturbed eating behavior, which is mostly observed among dieting women, and is integrated with appetite disorder, and uncontrolled eating of plenty of junk food. The Compulsive Eating Scale (CES) created first by Kagan & Squires in 1984, is an eight-item self-reporting instrument that is made to measure the severity of binge eating disorder. The aim of this study was to provide the reliability and validity of the Persian version of Compulsive Eating Scale (CES) among overweight and obese women in Iran.